(3YbO GdOQQ aj YOO Bi GdShQs - (3HQgGf GdOjf EHQGgje Hf CHj HcQ GdLYHQj,J (B687 (3g` s ((3eMeO Hf YHO GdcQje GdNdjdi s)
(3ChdgG (B:s
(3bUjOI OGdjI ef HMQ GdWhjd ChdgG (B/ (3HMeO QHI ai CHJOi hEjGc GSJYjf jSjQ ebUOi s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B11 s
(3eUOQ GbJfGA GdCUd (B:s
(3JjehQjI (B((3JaSjQ (B571(1)) s
Keywords: (3GdbQGAGJ hGdJLhjOs